Conceptions of the border and behaviors of cross-border actors - Belkacem, Rachid; Boquet, Mathias; Dorkel, Nicolas; Renard-Grandmontagne, Colette; Siadou-Martin, Béatrice; Yildiz, Hélène (Projectics / Proyéctica / Projectique, 2022)
Abstract: „Based on the example of the Grande Région (Greater Region), this research note retains a systemic approach to the cross-border area and focuses on trade and consumption in this territory. It defines this space as a trade system in a border zone made up of actors (national and/or foreign distributors, consumers), places (sales outlets of varying size) registered in a territory, and practices (consumption practices, implementation strategies) that are in interaction. Four points are discussed. First, distance to the border is questioned, leading us to compare actors’ perceptions with the actual distance. Second, we examine the links between work, mobility, and consumption. The third section focuses on individuals as consumers and underlines the importance of psychological, sociological, and cultural variables. Finally, a focus on retailer strategies underlines the need to take into account specificities for the implementation of commercial strategies. This research note invites us to conduct further research on trade in the cross-border space by outlining the framework of a research agenda.“
Keywords: Grenzarbeitnehmer; Handel; Verbrauch

Les pratiques commerciales dans une région frontalière. Les exemples d’Arlon, de Luxembourg-ville et de Metz - Smits, Florence (Belgeo, 2006)
Abstract: „Parts of Belgium, France, Germany and Luxembourg which comprise the Great Region have witnessed an increase in the mobility of workers and in the degree of political collaboration. Nevertheless, this evolution does not seem to have had an impact on the consumption habits of workers who tend to remain quite different in Arlon, Luxembourg and Metz. In contrast, people with less mobility but more time available, such as the retired and young, seem to exhibit the same pattern of consumption.“
Keywords: Arlon; Einkaufen; Grenzarbeitnehmer; Handel; Luxemburg (Stadt); Metz; Mobilität; Verbrauch